PERMASALAHAN HUKUM PENGADAAN HAK ATAS TANAH UNTUK PEMBANGUNAN SARANA PENDUKUNG IBUKOTA NUSANTARA - Daru Trimustiko Sakti; Muhammad Efendy; Rahmida Erliyani (Collegium Studiosum Journal, 2023)
The problem of land is a problem that often occurs, especially in urban areas where the need for land continues to increase in proportion to the number of people living in urban areas. Procurement of land for various community needs such as infrastructure development, residential land, office land, industrial land and so on is a problem that is currently always faced and often gives rise to new problems. The transfer of Indonesia's capital city from Jakarta to the capital city of Nusantara has become a new problem regarding the procurement of land rights for the construction of a new capital city, where land that was not previously used as the national capital area has become the national capital area. Some things like Procedures for procuring land rights for the construction of supporting facilities for the capital of the Nusantara and regarding forms of legal protection that can protect land rights holders who receive compensation who are affected by the construction of supporting facilities for Nusantara Capital City are interesting matters to discuss. This research uses research methods empirical normative.